Porównanie metody gradientowej wykorzystującej transformację logistyczną z wybranymi metodami dyskryminacji - Trzęsiok, Joanna (Comparison of Gradient Boosting Method Using the Multiple Logistic Transform with Other Classification Methods, 2007)
The main subject of this paper is related to gradient boosting method using the multiple logistic transform. This is a method for classification, which is based о MART - the multiple additive regression trees. The goal of the article is to compare the presented method with other classification methods in terms of classification error generated by the final model. T analysis was conducted on some real and artificial benchmarking data sets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 245-252